Cortical thickness in de novo patients with Parkinson disease and mild cognitive impairment with consideration of clinical phenotype and motor laterality. (24th July 2015) - Danti, S.; Toschi, N.; Diciotti, S.; Tessa, C.; Poletti, M.; Del Dotto, P.; Lucetti, C.
Abstract : Background and purpose: Parkinson's disease (PD) is a progressive neurodegenerative disorder with motor and non‐motor symptoms, including cognitive deficits. Several magnetic resonance imaging approaches have been applied to investigate brain atrophy in PD. The aim of this study was to detect early structural cortical and subcortical changes in de novo PD whilst distinguishing cognitive status, clinical phenotype and motor laterality. Methods: Eighteen de novo PD with mild cognitive impairment (PD‐MCI), 18 de novo PD without MCI (PD‐NC) and 18 healthy control subjects were evaluated. In the PD‐MCI group, nine were tremor dominant and nine were postural instability gait disorder (PIGD) phenotype; 11 had right‐sided symptom dominance and seven had left‐sided symptom dominance. FreeSurfer was used to measure cortical thickness/folding, subcortical structures and to study group differences as well as the association with clinical and neuropsychological data. Results: Parkinson's disease with MCI showed regional thinning in the right frontal, right middle temporal areas and left insula compared to PD‐NC. A reduction of the volume of the left and right thalamus and left hippocampus was found in PD‐MCI compared to PD‐NC. PD‐MCI PIGD showed regional thinning in the right inferior parietal area compared to healthy controls. A decreased volume of the left thalamus was reported in PD‐MCI with right‐sided symptom dominance compared to PD‐NC and PD‐MCI with left‐sided symptom dominance. Conclusions: When MCI was present, PD patients showed a fronto‐temporo‐parietal pattern of cortical thinning. This cortical pattern does not appear to be influenced by motor laterality, although one‐sided symptom dominance may contribute to volumetric reduction of specific subcortical structures.